(untitled) (Global Journals of Research in Engineering, 2013)
This paper proposes a wireless ZigBee technology to monitor the parameters of the transformer. The transformer parameters such as voltage, current, power factor and temperature can be monitored through wireless ZigBee technology. Embedded Ethernet is used to develop client and server applications. Acquisition of voltages, currents, temperatures, active and reactive power, controlling the switching devices and acquired data processing can be done by an embedded system. The modules in the embedded system are connected and the images of the transmission lines of the transformer during the power transmission will be noted and compared with the standard IR images by the use of image processing to observe the level of temperature passing through the transmission lines. Active power and the reactive power of the transformer which specifies the power usage and power wastage of the transformer respectively can be monitored. MATLAB simulations are carried out for the parameter monitoring.